The ethnonyms ‘Bushman’ and ‘San’ - Peter Raper (Acta Academica, 2010)
The first part of the term “Bushman” has been variously explained as referring to bush-covered country, or to bushes as refuge from enemies, as cover from which to attack man or beast, or as dwelling places. The word boes is neither Afrikaans nor Dutch, and is probably a phonological adaptation. Several San ethnonyms mean “bush men” or “bush people”. The term San, a contraction of Sanqua, earlier Sonqua, has been explained as “gatherers”, “outcasts, pariahs”, “servants, subjects”, “aborigines or settlers”, and “those who sit and rest”. Van Riebeeck’s addition of the explanations Vismans (“fish men”), struyckroovers (“bandits”, literally “bushrobbers”) and Berghvolck (“mountain people”) to various mentions of Souqua, Soaqua and similar words, prompts the possibility of translations.